The Importance of Social Emotional Learning for Children and Adults - Rayhana; Wardani Rahayu; Rahmawati, Yuli (Sekolah Pascasarjana Universitas Negeri Jakarta, 2024)
Children's social and emotional development in the early years is crucial to help them learn how to become good, mature adults. Studies show that children who have a supportive home environment and have the opportunity to attend preschool early learning programs that support their overall development will have better performance at school and better life prospects in the long run. Emotional development at an early age is critical to overall brain development and has significant effects throughout life with a strong emotional foundation in managing everyday social interactions. Adults demonstrating good, social and emotional skills around them, is the best way to instill righteous values in children. Research shows that teachers are severely affected by poor physical and mental health issues as a result of the workload they face. Teachers who experience low job satisfaction result in poor student learning outcomes due to pressure on their mental health. Implementing SEL for teachers can help them overcome their frustrations and stress. In addition, SEL helps teachers perform their roles better, improving the classroom environment and overall climate, creating a safe environment for young people to grow. Parents, guardians, or community members who need to be involved in SEL initiatives. Studies have shown that students are more likely to adopt SEL practices if they see their parents acting in the same way. They also do better academically and socially.